Assessment of the Projects with Industry Program Elizabeth R. Reisner and Others. - Reisner, Elizabeth R. (Distributed by ERIC Clearinghouse, 1983)
A study evaluated the Projects With Industry (PWI) program. (Authorized in 1968 to provide funding opportunities to organizations for the purpose of assisting severely disabled persons in obtaining competitive employment, the PWI program has provided support to projects that involve private sector representatives in the design of placement, training, and other services for disabled individuals.) The sources of the information for the study included interviews with persons familiar with the operation of the PWI program, a review of program documents maintained by the Rehabilitation Services Administration, and visits to seven PWI project sites around the country. Based on the information collected and analyzed in the study, the PWI projects appear generally successful in meeting the program's goal of developing private sector linkages to assist disabled persons in achieving competitive employment, although quantitative information to verify the performance of specific projects is limited. Furthermore, no single type of organization was found to be more successful than others in accomplishing PWI goals. Rather, the diversity of organizations operating PWIs and the flexibility projects exhibited in providing services appear to be important factors in the PWI program's overall effectiveness. (MN)